Crustal recycling by subduction erosion in the central Mexican Volcanic Belt. (1st October 2015) - Straub, Susanne M.; Gómez-Tuena, Arturo; Bindeman, Ilya N.; Bolge, Louise L.; Brandl, Philipp A.; Espinasa-Perena, Ramón; Solari, Luigi; Stuart, Finlay M.; Vannucchi, Paola; Zellmer, Georg F.
Abstract: Recycling of upper plate crust in subduction zones, or 'subduction erosion', is a major mechanism of crustal destruction at convergent margins. However, assessing the impact of eroded crust on arc magmas is difficult owing to the compositional similarity between the eroded crust, trench sediment and arc crustal basement that may all contribute to arc magma formation. Here we compare Sr–Nd–Pb–Hf and trace element data of crustal input material to Sr–Nd–Pb–Hf–He–O isotope chemistry of a well-characterized series of olivine-phyric, high-Mg# basalts to dacites in the central Mexican Volcanic Belt (MVB). Basaltic to andesitic magmas crystallize high-Ni olivines that have high mantle-like 3 He/ 4 He = 7–8 Ra and high crustal δ 18 Omelt  = +6.3–8.5‰ implying their host magmas to be near-primary melts from a mantle infiltrated by slab-derived crustal components. Remarkably, their Hf–Nd isotope and Nd/Hf trace element systematics rule out the trench sediment as the recycled crust end member, and imply that the coastal and offshore granodiorites are the dominant recycled crust component. Sr–Nd–Pb–Hf isotope modeling shows that the granodiorites control the highly to moderately incompatible elements in the calc-alkaline arc magmas, together with lesser additions of Pb- and Sr-rich fluids from subducted mid-oceanic ridge basalt (MORB)-type altered oceanic crust (AOC). Nd–Hf mass balance suggests that the granodiorite exceeds the flux of the trench sediment by at least 9–10 times, corresponding to a flux of ⩾79–88 km 3 /km/Myr into the subduction zone. At an estimated thickness of 1500–1700 m, the granodiorite may buoyantly rise as bulk 'slab diapirs' into the mantle melt region and impose its trace element signature (e.g., Th/La, Nb/Ta) on the prevalent calc-alkaline arc magmas. Deep slab melting and local recycling of other slab components such as oceanic seamounts further diversify the MVB magmas by producing rare, strongly fractionated high-La magmas and a minor population of high-Nb magmas, respectively. Overall, the central MVB magmas inherit their striking geochemical diversity principally from the slab, thus emphasizing the importance of continental crust recycling in modern solid Earth relative to its new formation in modern subduction zones.